Livestock Goods and Bads: A Summary of the ILRI Annual Planning Meeting 2010 - International Livestock Research Institute (International Livestock Research Institute, 2010)
LRI staff get together every year to review important issues and priorities on its research agenda. The 2010 meeting was held in Addis Ababa in April 2010.